Hepatitis B and C infection in haemodialysis patients in Libya: prevalence, incidence and risk factors - Alashek, Wiam A.; McIntyre, Christopher W.; Taal, Maarten W. (BioMed Central, 2012)
Background: Patients receiving maintenance haemodialysis (HD) are at higher risk for acquiring Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) infections than the general population. Strict infection control measures are essential to prevent nosocomial transmission. We aimed to investigate the incidence and prevalence of HBV and HCV infection in the HD population of Libya as well as risk factors for infection. Methods: All adult patients receiving maintenance HD (n=2382) in Libyan dialysis centres (n=39) were studied between May 2009 and October 2010. Testing for Hepatitis B surface antigen (HBsAg) and anti-HCV antibodies was performed at initiation of dialysis and every 3–6 months thereafter. Patients who were sero-negative for HBV and HCV (n=1160) were followed up for 1 year to detect sero-conversions. Results: Participant median age was 49 years and 58% were male. 831 patients (34.9%) were sero-positive for HBV and/or HCV (anti-HCV positive 31.1%; HBsAg positive 2.6%; both positive 1.2%). Of the sero-positive patients 4.7% were known to be infected before the initiation of HD. The prevalence of HBV±HCV infection varied widely between HD centres from 0% to 75.9%. Sero-positive patients were younger, had longer time on dialysis and more previous blood transfusions. Prospective follow-up revealed an incidence of sero-conversion of 7.7% during 1 year (7.1% HCV; 0.6% HBV). Wide variation in rates of newly acquired infections was observed between dialysis centres. All new HBV cases were referred from centres already treating HBV infected patients. New HCV infections were reported in most centres but the rate of HCV sero-conversion varied widely from 1.5% to 31%. Duration of dialysis, history of previous renal transplant and history of receiving HD in another centre in Libya were significantly associated with sero-conversion. Conclusion: Patients on maintenance HD in Libya have a high incidence and prevalence of HCV infection and lower rates of HBV infection. The factors associated with HBV and HCV infection are highly suggestive of nosocomial transmission within HD units. Urgent action is required to improve infection control measures in HD centres and to reduce dependence on blood transfusions for the treatment of anaemia. Keywords: Haemodialysis, Hepatitis B, Hepatitis C, Incidence, Libya, Nosocomial infection, Prevalence